2004
DOI: 10.1128/aem.70.2.1059-1067.2004
|View full text |Cite
|
Sign up to set email alerts
|

Restriction Fragment Length Polymorphisms and Sequence Analysis: an Approach for Genotyping Infectious Pancreatic Necrosis Virus Reference Strains and Other Aquabirnaviruses Isolated from Northwestern Spain

Abstract: Reference strains of infectious pancreatic necrosis virus resembling the 10 recognized serotypes and local isolates of aquabirnaviruses isolated in northwestern Spain from reservoirs (mollusks) and from asymptomatic and carrier cultured fish were genotyped by restriction fragment length polymorphism (RFLP) and nucleic acid sequence analyses. The RFLP analysis yielded seven genogroups, each of which was clearly correlated with a serotype. Sequence analysis of the three open reading frames provided quite similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 22 publications
3
47
0
4
Order By: Relevance
“…This is particularly evident between the Chilean and the North American isolates (WB and DM) within genotype 4, where the clustering of Chilean isolates could suggest the formation of a fifth genotype. Similar tradeassociated transmissions of IPNV have been suggested for isolates from Spain, Japan, Iran, and Ireland, that show a great similarity with reference strains from the sources where these countries have imported salmonid fish and eggs (Cutrín et al 2004, Nishizawa et al 2005, Ruane et al 2009, 2015, Dadar et al 2013. Concordantly, the phylogenetic trees in these studies also showed grouping among the local isolates and the formation of minor clusters within genogroups.…”
Section: Discussionsupporting
confidence: 64%
“…This is particularly evident between the Chilean and the North American isolates (WB and DM) within genotype 4, where the clustering of Chilean isolates could suggest the formation of a fifth genotype. Similar tradeassociated transmissions of IPNV have been suggested for isolates from Spain, Japan, Iran, and Ireland, that show a great similarity with reference strains from the sources where these countries have imported salmonid fish and eggs (Cutrín et al 2004, Nishizawa et al 2005, Ruane et al 2009, 2015, Dadar et al 2013. Concordantly, the phylogenetic trees in these studies also showed grouping among the local isolates and the formation of minor clusters within genogroups.…”
Section: Discussionsupporting
confidence: 64%
“…Typing of aquabirnaviruses and betanodaviruses in this study (41,42,43). However, at present, this geographical distribution has been altered probably because of natural migrations of wild fish populations, the use of fish as feed in aquaculture, and/or commercial movements of fish stocks (3,5).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, this classification has been established by means of immunologic techniques, but the application of molecular techniques has proven to be more useful to type and characterize aquabirnaviruses [25] . Actually, seven genogroups of aquabirnaviruses have been proposed based on the analysis of the nucleotide sequences of the VP2/NS junction region of the viral A RNA segment [12] .…”
Section: Discussionmentioning
confidence: 99%